2015
DOI: 10.1016/j.pmedr.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

High mercury seafood consumption associated with fatigue at specialty medical clinics on Long Island, NY

Abstract: We investigated the association between seafood consumption and symptoms related to potential mercury toxicity in patients presenting to specialty medical clinics at Stony Brook Medical Center on Long Island, New York. We surveyed 118 patients from April–August 2012 about their seafood consumption patterns, specifically how frequently they were eating each type of fish, to assess mercury exposure. We also asked about symptoms associated with mercury toxicity including depression, fatigue, balance difficulties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…According to the Korea Food and Drug Administration (KFDA), the total mercury concentration in fish/shellfish and deep-sea fish should be below 0.5 ppm and 1 ppm, respectively [55]. The Stony Brook Medical Center in New York reported that consumption of high-mercury deep-sea fish such as shark, marlin, swordfish, mackerel, tuna, and tile fish was associated with development of fatigue and depressive symptoms [56]. The results of our stratified analysis showed that the association between blood mercury and depression was predominant at the lowest tertile of fish consumption in females.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Korea Food and Drug Administration (KFDA), the total mercury concentration in fish/shellfish and deep-sea fish should be below 0.5 ppm and 1 ppm, respectively [55]. The Stony Brook Medical Center in New York reported that consumption of high-mercury deep-sea fish such as shark, marlin, swordfish, mackerel, tuna, and tile fish was associated with development of fatigue and depressive symptoms [56]. The results of our stratified analysis showed that the association between blood mercury and depression was predominant at the lowest tertile of fish consumption in females.…”
Section: Discussionmentioning
confidence: 99%
“…Ilość ta jest mniejsza o ok. 5% w porównaniu do roku 2016, co wynika z niższych cen drobiu i wieprzowiny (tab. 2) [16]. Według prognoz import do Polski zagranicznych produktów pochodzenia morskiego ma wzrastać.…”
Section: Dyskusjaunclassified
“…Na polski rynek sprowadzane są głównie surowe ryby, które następnie są przetwarzane przez lokalnych producentów. Tuńczyk najczęściej jest spożywany przez Polaków w formie puszkowanej [16].…”
Section: Dyskusjaunclassified
“…[2][3][4] Mercury poisoning encephalopathy, which is characterized by numbness of limbs, ataxia, narrowed vision, and hearing difficulties, can result in death from heart failure in severe cases. [5] Cadmium (Cd) is a nonessential metal element in the human body that can cause both acute and chronic toxicity. [6,7] Acute cadmium toxicity manifests as acute gastrointestinal irritation, while chronic cadmium toxicity manifests as the inhibition of macrophage phagocytosis.…”
Section: Introductionmentioning
confidence: 99%